2004
DOI: 10.1074/jbc.m312254200
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Properties of the Asparaginyl Hydroxylase (FIH) in the Oxygen Sensing Pathway Are Distinct from Those of Its Prolyl 4-Hydroxylases

Abstract: The activity of hypoxia-inducible transcription factor HIF, an ␣␤ heterodimer that has an essential role in adaptation to low oxygen availability, is regulated by two oxygen-dependent hydroxylation events. Hydroxylation of specific proline residues by HIF prolyl 4-hydroxylases targets the HIF-␣ subunit for proteasomal destruction, whereas hydroxylation of an asparagine in the C-terminal transactivation domain prevents its interaction with the transcriptional coactivator p300. The HIF asparaginyl hydroxylase is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
327
6
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 386 publications
(367 citation statements)
references
References 29 publications
29
327
6
5
Order By: Relevance
“…Within this microenvironment, the relative contribution of the two hydroxylases, which require oxygen for activity, remains to be clarified. The estimated K m values for oxygen for the PHDs and FIH in vitro are quite different: 250 and 90 mM, respectively (Koivunen et al, 2003). Consistent with this work, a recent study showed in in vivo experiments, using the endogenous human HIF-1a protein, that both prolyl hydroxylation was more sensitive to inhibition to hypoxia (Hx) than asparaginyl hydroxylation (Tian et al, 2011).…”
Section: Introductionsupporting
confidence: 64%
“…Within this microenvironment, the relative contribution of the two hydroxylases, which require oxygen for activity, remains to be clarified. The estimated K m values for oxygen for the PHDs and FIH in vitro are quite different: 250 and 90 mM, respectively (Koivunen et al, 2003). Consistent with this work, a recent study showed in in vivo experiments, using the endogenous human HIF-1a protein, that both prolyl hydroxylation was more sensitive to inhibition to hypoxia (Hx) than asparaginyl hydroxylation (Tian et al, 2011).…”
Section: Introductionsupporting
confidence: 64%
“…40 Recognition and hydroxylation of the CAD by FIH-1 have also been reported to require a minimal substrate sequence of approximately 35 residues, including residues 788-822, which essentially spans sites 1 and 2. 29 Hydroxylation is markedly reduced by deletion of only a few residues from either the N-or C-terminus, demonstrating the importance of both site 1 and site 2 in FIH-1 binding and hydroxylation.…”
Section: Oxygen-dependent Regulation Of Hif-cad By Fih-1mentioning
confidence: 97%
“…Interestingly, since FIH-1 appears to have a higher affinity for O 2 than the PHDs based on in vitro experiments, 29 it follows that as the severity of hypoxia increases, the PHDs would be inactivated first, while FIH-1 would require more severe hypoxia to lose activity (Figure 4). Indeed, overexpressed FIH-1 can still exert a catalytic effect at 0.2% Figure 3 Normoxic silencing of the CAD by FIH-1-mediated hydroxylation.…”
Section: Oxygen-dependent Regulation Of Hif-cad By Fih-1mentioning
confidence: 99%
See 2 more Smart Citations